Critically constituting organization - Chan, Andrew, 1960- (Advances in organization studies, 2000)
In the past, contingency and neo-Marxist theorists of culture reduced culture to an effect of something other than itself and, as they made culture metaphorical, they constituted its object of inquiry -- a somewhat impossible pretension. This book extends the debate considerably. It does so through considering the work of Foucault in the context of the analysis of culture. While Foucault has had a considerable impact on organization studies, up to the present no text has systematically addressed what happens to organization culture when it encounter a Foucauldian gaze. Read this book and you wi.